PENGARUH PENERAPAN PEMBELAJARAN INKUIRI SOSIAL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SD (Studi Eksperimen Kuasi pada Pembelajaran Ilmu Pengetahuan Sosial) - Gartini, Nuryuni Gartini (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
The aim of this study is to comprehend the influnces of social inquiry learning implementation against student critical thinking skill. The population of this study is all of the fourth grade students at Bojongherang Cluster in Cianjur. The process of taking sample is done by purposive sampling and the result is two classes of sample. The fourth grade of Bojongherang 2 as an experiment class that applies social inquiry learning, while the fourth grade of Bojongherang 4 as a control class that applies a conventional learning strategies. The study’s datais inquired through the pretes ang posttes by essay examination. The result of this study shows that social inquiry learning implementation give a significant effect to increase student critical thinking skill. Based on statistical calculation we find the critical thinking skill of boys student is higher than the girls student. Beside that, student who have a parent as a merchant is better than the student who have a parent as a civil servant and an employee in the way of thinking. Its assumed that the merchant have an entrepreneur soul who have a creative and autonomously thinking.Key word: social inquiry learning, critical thinking skill.